تأثير التغذية الورقية بالبورون والزنك وحمض الهيومك في نمو وإزهار شجرة الزيتون صنف "الخضيري" - مخول جرجس; نداف محمد; زيدان علي; أبو الشملات ربى (Latakia University Journal -Biological Sciences Series, 2019)
The experiment was carried out during two seasons 2017,2018 on olive orchard in Alkalof area of Lattakia Governorate on khodeiry variety on 30 years old, with the aim of studying the effect of foliar spraying with boron, zinc and humic acid on tree growth and the impact on flowering and set fruits. These nutrients were sprayed individually or combined together on olive trees three time during the growing season. These elements were sprayed: boron(200ppm), zinc (75ppm) and humic acid (250ppm).In the same concentrations was measured average of (leaf area, length of shoot, numbers of flowers on panicle and shoot, proportion of hermaphrodite flowers ,percentage of the aviable pollen and set fruit. Through the satatistical analysis showed a significant increase of all productive indicators compared to the control. Treatments (HA+Zn+B) and (HA+Zn) showed asignificant increase in leaf area, and recorded asignificant increase in shoot length in (B),(Zn+B) and (HA+Zn+B) treatments. The results showed a significant increase in numbers of flowers on panicle and shoot in Boron foliar spray treatments, and in proportion of hermaphrodite flowers (90.33%) and , the percentage of the aviable pollen (93.67%) as average of two seasons, as the spraying treatments (HA+Zn+B) 6.84% and (HA+Zn)6.89% recorded a significant increase in set fruit. While control treatment recorded the minmum value in all the stuided parameters. نُفذت التجربة خلال موسمي 2017 و 2018 في بستان زيتون في منطقة القلوف التابعة لمحافظة اللاذقية على صنف "الخضيري" بعمر30 سنة بهدف دراسة تأثير التغذية الورقية بعنصري البورون والزنك وحمض الهيومك في نمو شجرة الزيتون ومدى تأثيرها على الإزهار وعقد الثمار. رشت هذه العناصر منفردة أو مجتمعة مع بعضها على الأشجار ثلاث مرات خلال موسم النمو في أوقات محددة؛ إذ رش البورون بتركيز 200ppm والزنك 75ppm ، وحمض الهيومك 250 ppm. حُسب متوسط مساحة الورقة ومتوسط الزيادة في طول الطرد منذ بدء التجربة حتى نهايتها في كل موسم، عدد الأزهار على العنقود الزهري وعلى الطرد، نسبة الأزهار الخنثى، وقدرت حيوية حبوب اللقاح، ونسبة العقد. من خلال نتائج التحليل الإحصائي لُوحظ زيادة معنوية في جميع المؤشرات المدروسة لمعاملات التغذية الورقية مقارنة بالشاهد؛ إذ أظهرت معاملة الرش (هيومك+(B+Zn ومعاملة الرش (هيومك+Zn) زيادة معنوية في مساحة الورقة، كما حققت زيادة معنوية في طول الطرد في معاملات (B) و ( (B+Zn و(هيومك+(B+Zn. أظهرت النتائج زيادة معنوية في عدد الأزهار في العنقود وعلى الطرد في معاملات التغذية الورقية بالبورون، كما تفوقت معاملات التغذية الورقية بالبورون في نسبة الأزهار الخنثى (90.33%)، وحيوية حبوب اللقاح (93.67%) كمتوسط موسمين، كما حققت معاملة الرش (هيومك+(B+Zn 6.84%، ومعاملة الرش (هيومك+Zn) 6.89% زيادة معنوية في نسبة العقد الأولي كمتوسط موسمين، بينما حققت معاملة الشاهد أدنى القيم في جميع المؤشرات المدروسة.